Does Antidiscrimination Law Influence Religious Behavior? An Empirical Examination - Barak-Corren, Netta (2016)
What role should the behavioral reality of conflicts regarding gender, sexuality, and religious convictions play in the theory and doctrine of antidiscrimination law? Although the past several decades have seen broadening tension between traditional beliefs and legal and societal norms—the most recent manifestation being Obergefell v. Hodges—almost no empirical work has been done to elucidate the behavioral reality of conflicts between religion and antidiscrimination law. This Article is the first empirical behavioral study on the decisions made by religious people under norm conflict. Drawing on two decision experiments with over 3500 religious individuals and in-depth interviews with senior religious managers, this Article examines the central theoretical explanations for why people (dis)obey the law. Is compliance more successfully achieved by improving the perceived fairness of judicial proceedings (as predicted by the procedural fairness theory) or by adjusting the outcomes of these proceedings (as predicted by the economic analysis theory)? Conventional wisdom assumes that greater fairness and milder outcomes would facilitate compliance. However, the data suggest that greater procedural fairness has little to no impact on compliance decisions, while milder outcomes that afford monetary penalties as substitutes for legal compliance are not perceived as more acceptable and actually erode adherence to legal norms rather than promoting it. This Article discusses the broader implications of my findings for religious accommodations, offering recommendations to lawmakers who wish to mitigate conflicts between law and religion without relinquishing fundamental legal commitments